Balancing macronutrient intake in a mammalian carnivore: disentangling the influences of flavour and nutrition. Issue 6 (June 2016) - Hewson-Hughes, Adrian K.; Colyer, Alison; Simpson, Stephen J.; Raubenheimer, David
Abstract : There is a large body of research demonstrating that macronutrient balancing is a primary driver of foraging in herbivores and omnivores, and more recently, it has been shown to occur in carnivores. However, the extent to which macronutrient selection in carnivores may be influenced by organoleptic properties (e.g. flavour/aroma) remains unknown. Here, we explore the roles of nutritional and hedonic factors in food choice and macronutrient balancing in a mammalian carnivore, the domestic cat. Using the geometric framework, we determined the amounts and ratio of protein and fat intake in cats allowed to select from combinations of three foods that varied in protein : fat (P : F) composition (approx. 10 : 90, 40 : 60 and 70 : 30 on a per cent energy basis) to which flavours of different 'attractiveness' (fish, rabbit and orange) were added. In two studies, in which animal and plant protein sources were used, respectively, the ratio and amounts of protein and fat intake were very consistent across all groups regardless of flavour combination, indicating regulation of both protein and fat intake. Our results suggest that macronutrient balancing rather than hedonistic rewards based on organoleptic properties of food is a primary driver of longer-term food selection and intake in domestic cats.